Turkish political parties and Turkish nationalism - Yesevi, Çağla Gül (My University, 2012)
This study will deal with the policies, discourses and actions of the Turkish political parties and their impacts on discources of Turkish nationalism. This study will evaluate the nationalisms of the Republican People’s Party (the RPP), the Nationalist Action Party (the NAP), and the Justice and Development Party (the JDP) of Turkey, especially during the first period of the JDP in power. Turkish nationalism has been represented by the RPP and the NAP. Nationalism of the NAP has been conservative, in that sense, the NAP supports traditional and Islamic values. The RPP has been the follower of the Kemalist principles. The Justice and Development Party (the JDP) pursues the necessities of the globalization process. It gives importance to internationalism, accession to the EU, integration with the global markets. Also, the JDP gives importance to Islamism and traditional values. Highlighting on some foreign policy issues as Iraq and Cyprus, changing attitudes of Turkish political parties will be explained. This study investigates different party discourses on those issues and tries to consider and evaluate Turkish nationalism of that era.
Keywords: Nationalism; political parties; Iraq; Cyprus